An analysis of incentive effects of national road infrastructure program on local economic development - Gella, Nixen Julius N.; Solon, Orville Jose C. (Quezon City School of Economics, University of the Philippines Diliman, 2024)
With autonomy, local governments are expected to become self-reliant communities. During the transition period, the national government provides intergovernmental transfers such as Internal Revenue Allotment (IRA) and national public road infrastructure program (NPRIP) to support devolved functions. In addition, the local revenue and expenditure program of other Local Government Units (LGUs) produce spillovers on each other's ability to generate own revenues. All these concerns are important in determining how to optimize their benefits against possible disincentive effects of national and inter-local transfers on own-source revenue. In trying to address this policy concern within the context of the implementation of the Local Government Code of 1991, this study estimates a two-way fixed effects within-group regression model of local real property tax (RPT) as a function of the presence of national roads, allocation of IRA in a locality, and local revenue and expenditure program of other LGUs while controlling for local characteristics using data of 70 provinces from the year 1992 to the year 2022. This study finds that NPRIP has a positive impact on RPT collection of Second Income Class provinces and above. Moreover, a one percent increase in the allotted IRA will result in a 0.66% increase in the provincial collected RPT. By defining neighbor provinces as those with the same Regional Classification, a one percent increase in the average neighbor IRA and RPT leads to a 0.83% decrease and a 0.89% increase in the collected provincial RPT, respectively. In addition, NPRIP produces inter-local competition between provinces, for all 70 provinces. By defining neighbor provinces as those with inter-provincial buses or ferries, a one percent increase in the average neighbor IRA leads to a 0.32% decrease in the collected RPT of the province. Furthermore, NPRIP only produces inter-local competition for provinces with Second Income Class neighboring provinces and above.
Thesis (Master in Development Economics) -- University of the Philippines Diliman; June 2024.
Keywords: Roads -- Philippines; Infrastructure (Economics) -- Philippines